Assessment of the reliability of bent reinforced concrete elements under corrosive effects - Dekhterev Denis; Matseevich Tatyana (E3S Web of Conferences, 2023)
The main problem of reducing the reliability and durability of reinforced concrete structures is the corrosion of concrete and reinforcement of operated buildings and structures. Calculation of structures made of reinforced concrete, taking into account environmental influences, is complicated by the stochastic nature of the parameters of corrosion processes. The conducted studies are aimed at solving the problem of improving the methodology of the probabilistic approach to the calculation of corrosion-damaged reinforced concrete elements. The article considers a probabilistic assessment of reliability for the most common bent reinforced concrete elements, taking into account corrosive wear and the time factor. The modeling of the effect of corrosion processes on the stress-strain state of a reinforced concrete element was carried out using the concrete deformation diagram, which takes into account the decrease in strength characteristics with an increase in the concentration of an aggressive medium in concrete. The scheme of propagation of an aggressive environment in concrete is adopted according to the diffuse front method. Corrosion processes in reinforcement were taken into account by reducing the effective cross-sectional area of reinforcing bars. The change in the properties of steel (its embrittlement) with an increase in the concentration of an aggressive medium was not taken into account. Reinforcement corrosion was simulated after the incubation period, after the concentration of the aggressive medium on the surface of the reinforcing bars reached a critical value. The determination of the moment of the onset of the limit state in the element was carried out on the basis of a nonlinear deformation model at each point of the section of the element to achieve the maximum possible tensile or compression strains in concrete and reinforcement. To solve the problem of reliability assessment, the method of statistical modeling implemented in a specialized software package was used. To apply this method, according to previous studies, the probabilistic parameters of all random variables were taken: mathematical expectation and standard deviation. Based on the results of the reliability assessment, graphs of the decrease in the reliability of a bent reinforced concrete element from the time of exposure to an aggressive environment were obtained.